Drugs during pregnancy and lactation : (Elsevier, 2007)
This book is the definitive source of information on the risks from almost all relevant drugs that might be taken by women of reproductive age. Risk is assessed not only for prescribed medicinal products for diseases, but also for toxins and narcotics, both before pregnancy as well as during pregnancy and lactation. This book also provides conclusive information on the safe use of drugs in order to prevent birth defects and covers more drugs/agents than any other book in the field.